A rare presentation of angioedema with isolated retropharyngeal and supraglottic involvement. Issue 1 (2nd January 2019) - Patel, H.; Kant, S.; Chow, R.
ABSTRACT: Angiotensin converting-enzyme (ACE) inhibitors are commonly prescribed drugs with multiple indications including congestive heart failure, hypertension, and diabetic nephropathy. ACE inhibitor induced angioedema is commonly seen across emergency departments and clinics, with transient swelling of lips, tongue, and other facial structures being the common presentation. Isolated airway obstruction as a result of pharyngeal and laryngeal swelling without facial swelling is a rare presentation. We present a case of a patient on lisinopril therapy for one year who experienced severe airway compromise without the classic symptoms of ACE inhibitor induced angioedema. He required emergent cricothyroidotomy to secure his airway, as fiberoptic laryngoscopy showed 90% obstruction and inability to visualize true vocal cords. His ACE inhibitor therapy was discontinued, and he was discharged home within a few days with no residual symptoms.